SOCIAL MEDIA AS A PLATFORM FOR LEARNING THE ARABIC LANGUAGE FOR GENERATION Z - Muhammad Jailani; Elal Sutri; R. Taufiqurrochman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The development of science and knowledge is marked by technological developments. One form of technological progress that is very rapid in this era is social media. Social media has penetrated aspects of people's lives, especially among Generation Z people. However, the use of social media is mostly only for existence purposes. So, in this case, the role of a professional educator is really needed, one who is able to adapt and utilize increasingly sophisticated technological developments in learning to achieve the learning goals that have been determined. So, this study aims to find out how social media is described as a forum for learning Arabic in Generation Z. This research uses qualitative methods with a descriptive approach. The data collection technique is in the form of library research, namely examining various problems from various library sources that are harmonious and appropriate and exploring information and data, which the author will present in the form of a discussion until a conclusion is reached. The results of this research show that social media can be used as a forum for Generation Z to learn Arabic. Generation Z can integrate social media into Arabic language learning by using social media as a learning medium. Various social media platforms that can be used to learn about Ara include Facebook, YouTube, Twitter, WhatsApp, Instagram, Telegram, and TikTok